Analysis of Mirrored Psychophysiological Change of Cardiac Surgery Team Members During Open Surgery - Kennedy-Metz, Lauren R. (J Surg Educ, 2020)
OBJECTIVE: Mirrored psychophysiological change in cognitive workload indices may reflect shared mental models and effective healthcare team dynamics. In this exploratory analysis, we investigated the frequency of mirrored changes, defined as concurrent peaks in heart rate variability (HRV) across team members, during cardiac surgery. DESIGN: Objective cognitive workload was evaluated via HRV collected from the primary surgical team during cardiac surgery cases (N=15). Root mean square of the successive differences (RMSSD) was calculated as the primary HRV measure. Procedures were divided into consecutive non-overlapping 5-minute segments, and RMSSD along with deviations from RMSSD were calculated for each segment. Segments with positive deflections represent above-average cognitive workload. Positive deflections and peaks across dyads within the same segment were counted. SETTING: Data collection for this study took place in the cardiovascular operating room during live surgeries. PARTICIPANTS: Physiological data was collected and analyzed from the attending surgeon, attending anesthesiologist, and primary perfusionist involved with the recorded cases. RESULTS: Of the 641 five-minute segments analyzed, 325 (50.7%) were positive deflections above average, concurrently across at least two team members. Within the 325 positive deflections, 26 (8%) represented concurrent peaks in HRV across at least two active team members. Mirrored peaks across team members was observed most commonly during the coronary anastomoses or valve replacement phase (N=12). CONCLUSIONS: In this pilot study, mirrored physiological responses representing peaks in cognitive workload were observed uncommonly across dyads of cardiac surgery team members (1.73 peaks/case on average). Almost half of these occurred during the most technically demanding phases of cardiac surgery, which may underpin teamwork quality. Future work should investigate interactions between technical and non-technical performance surrounding times of mirrored peaks and expand the sample size. ACGME COMPETENCIES: Systems-based practice